Moral Education Thoughts According to Mohammad Natsir - Nawang Lukman Priyonggo; Tobroni Tobroni; M. Nurul Humaidi (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2026)
This study aims to examine in depth Mohammad Natsir's thoughts on moral education and its relevance in the context of contemporary Islamic education. Mohammad Natsir is one of the prominent Indonesian Muslim thinkers and politicians who strongly emphasized the importance of moral development as the core of Islamic education. This study uses a qualitative approach with a library study method, namely analyzing Natsir's works and other relevant literature, and combining them with the thoughts of classical figures such as Al-Ghazali as a comparison. The results show that according to Natsir, moral education does not only aim to distinguish between good and bad, but also to shape individuals who are faithful, knowledgeable, and have noble morals. Moral education must be based on strengthening faith, good deeds, and exemplary behavior, and implemented holistically through the integration of spiritual, intellectual, and social aspects. Natsir also emphasized the important role of education in building Islamic civilization by fostering individuals who are responsible to themselves, society, and God. Natsir's thoughts on moral education have proven to be still highly relevant in addressing the challenges of the moral crisis in the modern era. Values such as honesty, integrity, discipline, and social concern that he offers are in line with the principles of character education in current national education policy.